Bounds tests of the theory of purchasing power parity - Coe, Patrick J.; Serletis, Apostolos (Journal of Banking & Finance, 2002)
In this paper we test the absolute and relative purchasing power parity (PPP) hypotheses during the recent flexible exchange rate period, using quarterly data for 21 OECD countries. In doing so, we use a new econometric technique developed by M.H. Pesaran et al. [Bounds testing approaches to the analysis of long run relationships. University of Cambridge, Department of Applied Economics, Working Paper #9907]. This approach is particularly interesting as it is capable of testing the existence of long-run relations regardless of whether the underlying variables are stationary, integrated, or mutually cointegrated.